Development of Acceptance and Commitment Therapy Group Counseling Models and Mindfulness-Based Stress Reduction to Reduce Academic Burnout in High School Students - Sofyan, Afriyadi; Ramli, M; Sugiyo, Sugiyo; Kurniawan, Kusnarto (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
The current pandemic has an impact on mental health, especially students who do online learning. In relation to burnout, this study aims to integrate Acceptance and Commitment therapy and Mindfulness-Based Stress Reduction to reduce burnout, experiments were carried out in groups for the application of ACT while MBSR materials were given online and practised independently by each counselee after face-to-face meetings were held. This study uses educational design, research and development (Educational Research & Development), which is a research design that aims to produce or develop a product in the form of models, designs, prototypes, materials, media, tools or strategies, in order to improve the quality of learning. The educational R&D research design has ten stages as proposed by Borg & Gall. The stages are simplified and grouped into three stages, namely (1) Preliminary Study, (2) Development Phase, and (3) Validation Phase. The results of this study revealed that group counseling by applying Acceptance and Commitment therapy and Mindfulness-Based Stress Reduction was proven to be able to reduce burnout. With the findings of this study, school counselors can make group counseling integrate ACR and MBSR therapy as an alternative to reduce student academic burnout at school